Clinical teaching: the case of bedside rounds - Giannasi , Sergio; Durante, Eduardo (Revista del Hospital Italiano de Buenos Aires, 2012)
Possibly, bedside teaching in medicine is as old as medicine itself. Through history, well-known professors like F.Silvio and Sir W. Osler considered the strength of this teaching strategy and promoted it extensively. In the modern age, it is recognized that bedside teaching covers a variety of aspects that can not be taught in the classroom, such as learning of communication skills, physical examination, etc.; but at the same time, multiple barriers to its successful implementation have been identified. In this article, we describe the most common barriers that teachers should overcome to promote a meaningful and deep learning; as well as a series of practical proposals that are indicated to favor a proper implementation
Keywords: teaching and learning in clinical settings; bedside teaching; bedside rounds revisited; work-based learning; ward rounds; clinical skills